2019
DOI: 10.1021/acs.accounts.9b00221
|View full text |Cite
|
Sign up to set email alerts
|

From Dyestuff Chemistry to Cancer Theranostics: The Rise of Rylenecarboximides

Abstract: CONSPECTUS: Fighting cancer with the means of chemistry remains a tremendous challenge and defines a pressing societal need. Compounds based on synthetic organic dyes have long been recognized as vital tools for cancer diagnosis and therapy (theranostics). Fluorescence and photoacoustic imaging of cancer as well as cancer treatment protocols such as photodynamic and photothermal therapy are all photobased technologies that require chromophores. However, a serious drawback of most chromophoric molecules is phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 56 publications
0
109
0
1
Order By: Relevance
“…Besides the encapsulation of organic radicals as guest molecules, the fabrication of ordered supramolecular structures based on organic radials can also provide steric protection to the radicals. Yin et al reported the use of a perylenediimide (PDI) derivative and Zr-cluster to fabricate a metal-organic framework Zr-PDI 55,56 (Fig. 9).…”
Section: Steric Protection By Host-guest Chemistrymentioning
confidence: 99%
“…Besides the encapsulation of organic radicals as guest molecules, the fabrication of ordered supramolecular structures based on organic radials can also provide steric protection to the radicals. Yin et al reported the use of a perylenediimide (PDI) derivative and Zr-cluster to fabricate a metal-organic framework Zr-PDI 55,56 (Fig. 9).…”
Section: Steric Protection By Host-guest Chemistrymentioning
confidence: 99%
“…In addition to the great extensibility for development as diverse modes of chemosensors targeting broad range of environment analytes, PDI-based materials also possess other unique features, such as remarkably strong thermal/chemical/photochemical stability, environment benignity, good biocompatibility, and low cytotoxicity [3,37,[62][63][64]. Indeed, due to these superior features (compared to most of other chemosensors), PDI-based fluorescence and colorimetric sensors, as well as the related molecular probes, have already been extensively employed in physiological and food detections [62], cell imaging and related biological probing [22,30,33,35,37,40], and biomedical imaging and photodynamic therapy [63,64]. Moreover, the great success of PDI-based sensors in liquid-phase detection can be extended onto development of solid-phase sensors, e.g., thin films, which will further mitigate the risk of toxicity impact to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…82 Several rylenecarboximides (PDI, TDI, and QDI) based photothermal agents have been developed for photoacoustic imaging-guided PTT. [83][84][85][86] Through π-conjugation extension or construction of D-π-A structures, dyes with higher photothermal conversion efficiencies (up to 64%) can be obtained ( Figure 8A). 86 Especially, TDI and QDI based photothermal agents can self-assemble into ultrasmall nanoparticles (∼10 nm), favoring for deep penetration of tumor tissues and achieved high resolution tumor photoacoustic images.…”
Section: Imaging-guided Phototherapymentioning
confidence: 99%